Power: Divine and Human : Christian and Muslim Perspectives - Marshall, David, 1963-; Mosher, Lucinda (Book collections on Project MUSE., 2019)
This is the next volume of the Building Bridges Seminar. As is always the case, Power--Divine and Human: Christian and Muslim Perspectives comprises pairs of essays by Christians and Muslims which introduce texts for dialogical study, plus the actual text-excerpts themselves. This new book goes far beyond mere reporting on a dialogical seminar; rather, it provides guidance and materials for constructing a similar dialogical experience on a particular topic. As a resource for comparative theology, Power--Divine and Human is unique in that it takes up a topic not usually explored in depth in Christian-Muslim conversations. It is written by scholars for scholars. However, in tone and structure it is suitable for the non-specialist as well. Students (undergraduate and graduate), religious leaders, and motivated non-specialists will find it readable and useful. While it falls solidly in the domain of comparative theology, it can also be used in courses on dialogical reading of scripture, interreligious relations, and political philosophy.